Anxiety in the Perinatal Period: Associated Factors - Rocío Navas-Arrebola; Susana Blanco-López; Laura Peteiro-Mahía; Noelia López-Castiñeira; Sonia Pertega-Díaz; Teresa Seoane-Pillado (Clinical and Experimental Obstetrics & Gynecology, 2024)
Background: Attention to mothers during pregnancy, childbirth, and postpartum has focused on the physical aspects, overlooking mental health, which is critical to maternal well-being and childbirth. The aim of this study was to analyze the levels of anxiety experienced during labor and within the first 24 hours post-delivery, in order to identify the associated social and clinical factors associated with such anxiety. Methods: We performed a prospective observational follow-up study involving 448 women. Validated state and trait anxiety questionnaires, namely State-Trait Anxiety Inventory (STAI), which were employed in the study participants. All tests were performed with a bilateral approach. The p-values < 0.05 were considered significant. Statistical analysis was performed with the Statistical Package for the Social Sciences (SPSS, v.22.0, IBM Corp, Chicago, IL, USA). Results: State anxiety was more frequent among primiparous pregnant women, individuals who did not attend maternal education classes, and those with a history of prior abortion or cesarean section. Additionally, a significant association was observed with a history of mental disorder. Concerning Trait anxiety, significantly higher levels of anxiety were found in women with lower levels of education and in patients with a history of mental health issues. At 24 hours postpartum, elevated anxiety was more frequent in primiparous and significantly more frequent in patients with difficult deliveries, women whose infants were admitted to the Neonatal Intensive Care Unit (NICU), those lacking skin-to-skin contact, and those with previous mental health disorders. Conclusions: Insufficient maternal education, along with a complicated birthing process requiring infant hospitalization, both contribute to elevated levels of postpartum anxiety.